Prevalence, Virulence, Antimicrobial Resistance, and Molecular Characterization of Pseudomonas aeruginosa Isolates From Drinking Water in China - Wei, Lei; Wu, Qingping; Zhang, Jumei; Guo, Weipeng; Gu, Qihui; Wu, Huiqing; Wang, Juan; Lei, Tao; Xue, Liang; Zhang, Youxiong; Wei, Xianhu; Zeng, Xiaocong (Frontiers in Microbiology, 2020)
Pseudomonas aeruginosa is an important opportunistic pathogen, and remains a major threat to microbial safety of drinking water. There is a lack of comprehensive data on P. aeruginosa contamination in drinking water in China. Therefore, this study aimed to determine the prevalence, genetic diversity, virulence genes, and antimicrobial resistance of P. aeruginosa isolated from mineral water and spring water in China. From January 2013 to January 2014, 314 drinking water samples were collected from 23 cities in China. Of the collected samples, 77 (24.5%) were contaminated with P. aeruginosa and these comprised 34 source water (30.4%), 39 activated carbon filtered water (30.6%), and 4 final water product (3.9%) samples. A total of 132 P. aeruginosa isolates were obtained, and all of them showed presence of virulence genes, with the detection rates of ExoU, ExoS, phzM, toxA, and lasB genes being 7.6%, 86.3%, 95.5%, 89.4%, and 100% respectively. All isolates were sensitive to the 14 antibiotics (ciprofloxacin, levofloxacin, ofloxacin, norfloxacin, gentamicin, tobramycin, amikacin, polymyxin B, imipenem, meropenem, aztreonam, ceftazidime, cefepime, piperacillin/tazobactam) tested. The 132 isolates were categorized into 42 sequence types according to multilocus sequence typing, and ST235 accounted for 8.3% (11) of the total isolates. Thus, this study provides comprehensive data on the prevalence and characteristics of P. aeruginosa in drinking water in China, and can aid in developing preventive measures against contamination during the drinking water treatment process.